PENGARUH PEMBERIAN IMUNISASI DPT TERHADAP KENAIKAN SUHU TUBUH BAYI DI PUSKESMAS PURBOLINGGO LAMPUN - cynthia puspariny; Desi Kurniati; Gusti Ayu RY (Jurnal Ilmu Keperawatan dan Kebidanan, 2021)
Immunization is one of the preventive efforts in preventing diseases early on. Where a newborn baby has immunity that is not perfect so that it will increase the risk of infection. One of the immunizations that must be given to babies is DPT which can prevent diphtheria and tetanus.If a baby is infected with the disease, there is a high risk of developing growth and development disorders that can result in death. However, immunization will cause side effects in the form of fever in infants due to the process of antibody formation, so the baby will tend to be fussy when after immunization. The purpose of this research is to find out whether there is an effect of giving immunization to the rise in baby's body temperature. This research method uses experimental design in which the variables studied are DPT immunization as an independent variable and an increase in body temperature. The population in this study were infants who received DPT immunization, as many as 16 infants with a sampling technique using the cocecutive sampling method. The instrument used was the baby KMS observation sheet and temometer.Researchers conducted a bivariate analysis using a paired test, using a significance level of 95% or with a p-value ratio of a = 0.05.The results of the study note that there is an effect of DPT immunization on the rise in baby's body temperature obtained p-value that is 0,000 so it can be concluded that the p-value of 0,000 (0.05) thus Ha is accepted. It is expected that the mother continues to provide immunization to her baby so that the baby is protected from disease infections and can grow and develop optimally.